Head tremor and progressive multifocal leukoencephalopathy in AIDS patients: report of two cases Tremor cefálico e leucoencefalopatia multifocal progressiva em pacientes com SIDA: relato de dois casos - Carlos R.M. Rieder; Sofia C. Ziomkowski (Arquivos de Neuro-Psiquiatria)
Progressive multifocal leukoencephalopathy (PML) is caused by replication of JC virus in oligodendrocytes of immunocompromised patients. Common manifestations are focal motor and sensory deficits, gait abnormalities, speech and language disturbances, cognitive disorders, headache, and visual impairment. Although the occurrence of movement disorders is rare in PML, bradykinesia, rigidity, dystonia, myoclonic jerks and myoclonic ataxia have been described. Head tremor associated with PML has not been previously reported. We report two cases of PML in whom head tremor was present. A leucoencefalopatia multifocal progressiva (LMP) é causada pela replicação do vírus JC em oligodendrócitos de pacientes imunocomprometidos. As manifestações mais comuns incluem déficits motores e sensitivos, alterações da marcha, da fala e da linguagem, cefaléia e distúrbios visuais e cognitivos. Embora a presença de distúrbios do movimento não seja tão freqüente na LMP, bradicinesia, rigidez, abalos mioclônicos e ataxia mioclônica já foram descritos. Nós relatamos dois casos de LMP associados com tremor cefálico.